2017
DOI: 10.1093/jmammal/gyx052
|View full text |Cite
|
Sign up to set email alerts
|

Mismeasured mortality: correcting estimates of wolf poaching in the United States

Abstract: Measuring rates and causes of mortalities is important in animal ecology and management. Observing the fates of known individuals is a common method of estimating life history variables, including mortality patterns. It has long been assumed that data lost when known animals disappear were unbiased. We test and reject this assumption under conditions common to most, if not all, studies using marked animals. We illustrate the bias for 4 endangered wolf populations in the United States by reanalyzing data and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
131
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(137 citation statements)
references
References 14 publications
3
131
3
Order By: Relevance
“…In another example, Creel et al (2016a) argued that policy governing wolves-perhaps the most politically charged of all carnivores-in the United States does not adequately address hunting threats. Specifically, hunting policies could lead to population declines and do not align with ecological theory or data (Creel et al 2016a;Treves et al 2017a).…”
mentioning
confidence: 99%
“…In another example, Creel et al (2016a) argued that policy governing wolves-perhaps the most politically charged of all carnivores-in the United States does not adequately address hunting threats. Specifically, hunting policies could lead to population declines and do not align with ecological theory or data (Creel et al 2016a;Treves et al 2017a).…”
mentioning
confidence: 99%
“…Therefore, interactions between human causes of death are important to our understanding of the intended and unintended effects of predator removal, as are the effects of interventions meant to curb human causes of mortality. For example, poaching (illegal killing by people) was found to be the major cause of mortality in four endangered wolf populations of the USA, and unregulated killing was the major cause in one Alaskan sub-population (Adams et al, 2008;Treves et al, 2017a). Those studies also revealed that poaching was systematically under-estimated by traditional measures of risk and hazard or that mortality of marked animals differed from that of unmarked animals under legal, lethal management regimes (Schmidt et al, 2015;Treves et al, 2017c;Santiago-Ávila, 2019;Treves, 2019a).…”
Section: Does One Source Of Predator Removal Affect Other Sources Of mentioning
confidence: 99%
“…That practice continues today to protect domestic animals and crops from predators, although predators are now recognized for playing major roles in sustaining diversity and improving ecosystem resilience (Estes et al, 2011). Humans are the major cause of mortality of terrestrial carnivores globally, including extirpation, several cases of extinction of species, and protracted risks of extinction despite endangered species protections (Woodroffe and Ginsberg, 1998;Chapron et al, 2014;Treves et al, 2017a). Predator control plays a major role in human-induced mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treves et al. () reviewed 4 other cases in which inaccurate measurement of poaching led governments to downplay the major threat to endangered gray wolves ( Canis spp.). Predators in particular seem to be targets for the idea that hunting itself is a conservation intervention (Fig.…”
mentioning
confidence: 99%